The partner pay gap: Associations between spouses' relative earnings and life satisfaction among couples in the UK - Vanessa Gash; Anke C. Plagnol (The Economic and Social Research Institute (ESRI), 2019)
Despite women's recent gains in education and employment, husbands still tend to out-earn their wives. This article examines the relationship between the partner pay gap, i.e. the difference in earned income between married, co-resident partners, and life satisfaction. Contrary to previous studies, we investigate the effects of recent changes in relative earnings within couples as well as labour market transitions. Using several waves of the UK Household Longitudinal Study, we reveal that men exhibit an increase in life satisfaction in response to a recent increase in their proportional earnings. For women their proportional earnings had no effect on life satisfaction in one model, and in a model that accounted for their recent employment changes, women exhibited decreased life satisfaction. We also find secondary-earning husbands report lower average life satisfaction than primary-earning men, while such differences were not found for women. The analysis offers compelling evidence of the role of gendered norms in the sustenance of the partner pay gap.
Keywords: 330; couples' subjective well-being; household specialisation; income comparisons; life satisfaction; partner pay gap; relative earnings